G-C3N5 modified nano-hydroxyapatite material as well as preparation method and application thereof

By combining g-C3N5 with nano-hydroxyapatite, modified nanomaterials were prepared, which solved the performance limitations of pure hydroxyapatite in the field of photocatalysis and achieved the effect of efficient removal of environmental pollutants under visible light.

CN119215957APending Publication Date: 2024-12-31NANTONG VOCATIONAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Pure hydroxyapatite materials have limitations in mechanical properties, chemical stability and biological activity, which limit their application performance and effectiveness in the field of photocatalysis.

Method used

G-C3N5 is used as a modifier to combine with nanohydroxyapatite, and a g-C3N5 modified nanohydroxyapatite material is prepared by one-step calcination method, improving its energy band structure and expanding its response range to light.

Benefits of technology

It achieves efficient excitation of electron-hole pairs under visible light, improves the efficiency of photocatalytic degradation of environmental pollutants such as rhodamine B and methylene blue, and overcomes the defect of nano-hydroxyapatite only responding to ultraviolet light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215957A_ABST
    Figure CN119215957A_ABST
Patent Text Reader

Abstract

The invention provides a g-C3N5 modified nano-hydroxyapatite material as well as a preparation method and application thereof, and relates to the technical field of photocatalytic materials as well as preparation and application thereof. The material is composed of nano-hydroxyapatite and g-C3N5, the nano-hydroxyapatite is a photocatalytic material matrix, and the g-C3N5 is a modifier. The preparation process can be completed by only adopting one-step calcination, the preparation steps are extremely simple, and the cost is low. The efficient visible light response performance of the g-C3N5 overcomes the defect that the nano-hydroxyapatite only responds to ultraviolet light, electron-hole pairs can be excited under visible light, meanwhile, the positions of a conduction band and a valence band of the g-C3N5 and the positions of a conduction band and a valence band of the nano-hydroxyapatite can be staggered, transmission of excited electrons is facilitated, the recombination probability is reduced, and the photoelectric conversion efficiency is improved. Therefore, the photocatalytic activity is improved. The g-C3N5 modified nano hydroxyapatite material has a relatively good photodegradation property on various colored dyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials and preparation and application thereof, and specifically relates to a g-C3N5 modified nano hydroxyapatite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of nanotechnology, nanomaterials have shown wide application potential in many fields due to their unique physical and chemical properties. In particular, nano-hydroxyapatite (HAP), as an important bioactive material, has been widely studied and applied in the biomedical field, such as bone defect repair, tooth repair and drug carrier, because it is similar to the main components of human bones and teeth. The chemical formula of hydroxyapatite is Ca 10 (PO4)6(OH)2 is a calcium phosphate salt that is slightly soluble in water and belongs to the hexagonal system. The crystals are hexagonal columns, and the aggregates are blocky, granular or nodular. In its structure, the phosphorus-oxygen tetrahedral groups are tightly combined to form two channels with different diameters, 0.25 nm and 0.30-0.45 nm respectively. These channels are composed of different amounts of Ca 2+ The chemical composition of hydroxyapatite gives it unique chemical activity, such as the weakly alkaline sites on its surface (PO4 3- O 2- and OH - ) and weakly acidic sites (unsaturated coordinated Ca 2+ ), which allows hydroxyapatite to be + and reduce OH - To neutralize the charge imbalance caused by the loss of Ca2+. Hydroxyapatite has strong ion exchangeability, and the Ca2+ in its lattice structure 2+ It can be replaced by other cations, thereby adjusting the acid-base site and acid-base strength of hydroxyapatite. The optical properties of hydroxyapatite enable it to effectively absorb light energy and generate photogenerated electron and hole pairs during photocatalysis. These carriers can participate in redox reactions. As an excellent photocatalyst, hydroxyapatite can be used to degrade organic pollutants such as dyes, pesticides and antibiotics, and can also be used in the fields of photolysis of water to produce hydrogen, carbon dioxide reduction and killing bacteria and viruses.

[0003] However, pure hydroxyapatite has certain limitations in terms of mechanical properties, chemical stability and biological activity, which restricts its performance and effect in practical applications. In order to overcome these limitations, researchers have tried to modify HAP through various methods to improve its comprehensive performance.

[0004] Huazhong University of Science and Technology's invention patent ZL202410492913.3 discloses a zinc-doped hydroxyapatite nanowire and a preparation method, which can be used as a bone repair material with anti-inflammatory and antibacterial effects. Northeast Forestry University's invention patent ZL202410441583.5 discloses a method for preparing a rare earth-doped nanohydroxyapatite / zirconium dioxide composite material, which acts as a bone repair or oral hard tissue repair material. Yangzhou University's invention patent ZL2024104759240 discloses a preparation method and application of a polylactic acid / hydroxyapatite microsphere material. Xi'an Jiaotong University's invention patent ZL2023110942056 discloses a titanium dioxide / hydroxyapatite photocatalytic self-cleaning coating, coating and its preparation method, which has a certain self-cleaning effect. From the current patents, there are few reports on the application of hydroxyapatite-based materials in the field of photocatalysis. Liu et al. reported a Fe-doped hydroxyapatite prepared by ion exchange technology, which showed high photocatalytic activity in the degradation of rhodamine B (RhB) (10.1016 / j.matlet.2014.09.018). Shu et al. also prepared similar materials by hydrothermal method (10.1016 / j.cej.2023.141474). Adhitiyan et al. prepared Zn- and Ag-doped hydroxyapatite by microwave radiation and studied its degradation effect on rhodamine B and methylene blue under ultraviolet light (10.1016 / j.chphi.2024.100695).

[0005] The carbon nitrogen compound g-C3N5 composed of triazine and triazole units is a two-dimensional material with good photocatalytic performance, thermal stability and chemical stability. Its unique electronic structure and surface properties make it an ideal modifier. Although Xu et al. reported the use of g-C3N4 as a modifier to prepare g-C3N4 / hydroxyapatite composites and applied them in the rapid degradation of tetracycline (10.1016 / j.apcatb.2019.01.020), similar work was reported by Mohammad et al. (10.1016 / j.mtcomm.2022.104788) and Govindasamy et al. (10.1038 / s41598-022-15799-y), however, to date, there has been no report on the materials, preparation methods and applications of g-C3N5 modified hydroxyapatite for the preparation of photocatalysts.

[0006] In view of the above background and research status, the present invention is proposed. Summary of the invention

[0007] One of the purposes of the present invention is to provide a g-C3N5-modified nanohydroxyapatite material, which is composed of nanohydroxyapatite and g-C3N5, wherein the nanohydroxyapatite is a photocatalytic material matrix and the g-C3N5 is a modifier. The function of the modifier is to improve the energy band structure of the nanohydroxyapatite, promote the separation of photogenerated electrons and holes, and expand the response range of the nanohydroxyapatite to light.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned material, the preparation process can be completed by only one step of calcination, the preparation steps are extremely simple and the cost is low.

[0009] The third object of the present invention is to provide an application of the above material in removing environmental pollutants.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, the present invention provides a g-C3N5-modified nano-hydroxyapatite material, which is composed of nano-hydroxyapatite and g-C3N5, wherein the nano-hydroxyapatite is a photocatalytic material matrix and the g-C3N5 is a modifier.

[0011] In a second aspect, the present invention provides a method for preparing a g-C3N5 modified nano-hydroxyapatite material, comprising the following steps: Nano-hydroxyapatite and 3-amino-1,2,4-triazole were weighed, ground in a mortar, and then transferred into a crucible with a lid. The mixture was calcined at 500° C. in a muffle furnace for 3 hours. The product was washed and vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

[0012] Nano-hydroxyapatite is commercially available or synthesized in the laboratory.

[0013] In some embodiments, the mass ratio of nano-hydroxyapatite to 3-amino-1,2,4-triazole is (50~1):1.

[0014] Preferably, the mass ratio of nano-hydroxyapatite to 3-amino-1,2,4-triazole is 5:1.

[0015] In a third aspect, the present invention provides an application of a g-C3N5-modified nano-hydroxyapatite material prepared by the above-mentioned preparation method in the field of removing environmental pollutants.

[0016] The environmental pollutants include at least one of dyes such as rhodamine B and methylene blue.

[0017] The beneficial effects of the technical solution provided by the present invention are as follows: the present invention modifies nanohydroxyapatite by a modified material g-C3N5 having visible light response, thereby forming a g-C3N5 modified nanohydroxyapatite material. The efficient visible light response performance of g-C3N5 overcomes the defect that nanohydroxyapatite only responds to ultraviolet light, and can excite electron-hole pairs under visible light. At the same time, its conduction band and valence band positions can be dislocated with the conduction band and valence band positions of nanohydroxyapatite, which is conducive to the transmission of excited electrons and reduces the probability of recombination, thereby achieving efficient photocatalytic degradation, especially efficient removal of environmental pollutants such as rhodamine B, methylene blue, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the X-ray diffraction pattern of the sample obtained in Example 1 of the present invention.

[0019] Figure 2 This is the energy band structure diagram of the sample obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0022] The reagents and raw materials used in the present invention are shown in Table 1 below: Table 1 Reagents and raw materials used in the present invention Reagent name Molecular formula Specification Manufacturer (Origin) Nano-hydroxyapatite <h2 style=";text-align:left;direction:ltr"><![CDATA[HCa5O <h2 style=";text-align:left;direction:ltr"> 13 <h2 style=";text-align:left;direction:ltr"> P3]]><h2 style=";text-align:left;direction:ltr"> 97% Aladdin Chemical Reagent Co., Ltd. 3-Amino-1,2,4-triazole <![CDATA[C2H4N4]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. Anhydrous ethanol <![CDATA[C2H6O]]> Analytical grade Sinopharm Chemical Reagent Co., Ltd. Deionized water <![CDATA[H2O]]> <![CDATA[S<5 μs·cm -1 ]]> Hangzhou Wahaha Group Co., Ltd. Example 1

[0023] Weigh 5 g of nano-hydroxyapatite and 1 g of 3-amino-1,2,4-triazole, grind them in a mortar, transfer them into a crucible with a lid, and calcine them at 500 °C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times, and then vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

[0024] Take 0.1 g of the prepared g-C3N5-modified nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and irradiate the solution at a distance of 20 cm from the liquid surface for 30 minutes. After centrifugation, the degraded solution is measured by a UV-visible spectrophotometer at 554 nm to determine its absorbance. The degradation rate of rhodamine B is calculated to be 98.2%. Example 2

[0025] Weigh 5 g of nano-hydroxyapatite and 1 g of 3-amino-1,2,4-triazole, grind them in a mortar, transfer them into a crucible with a lid, and calcine them at 500 °C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times, and then vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

[0026] Take 0.1 g of the prepared g-C3N5-modified nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L methylene blue solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and irradiate the solution at a distance of 20 cm from the liquid surface for 30 minutes. After centrifugation, the solution after degradation has its absorbance at 664 nm determined by a UV-visible spectrophotometer. The degradation rate of methylene blue is calculated to be 94.3%. Example 3

[0027] Weigh 5 g of nano-hydroxyapatite and 0.1 g of 3-amino-1,2,4-triazole, grind them in a mortar, transfer them into a crucible with a lid, and calcine them at 500 °C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times, and then vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

[0028] Take 0.1 g of the prepared g-C3N5-modified nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and irradiate the solution at a distance of 20 cm from the liquid surface for 30 minutes. After centrifugation, the solution after degradation has an absorbance of 554 nm determined by a UV-visible spectrophotometer. The degradation rate of rhodamine B is calculated to be 68.7%. Example 4

[0029] Weigh 1 gram of nano-hydroxyapatite and 1 gram of 3-amino-1,2,4-triazole, grind them in a mortar, transfer them into a crucible with a lid, and calcine them at 500°C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times, and then vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

[0030] Take 0.1 g of the prepared g-C3N5-modified nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and illuminate for 30 minutes at a distance of 20 cm from the liquid surface. After centrifugation, the degraded solution is measured by a UV-visible spectrophotometer at 554 nm. The degradation rate of rhodamine B is calculated to be 82.4%. Comparative Example 1

[0031] Take 0.1 g of nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-watt xenon lamp light source (equipped with a λ≧420 nm filter) and illuminate for 30 minutes at a distance of 20 cm from the liquid surface. After centrifugation, the degraded solution is measured by a UV-visible spectrophotometer at 554 nm. The degradation rate of rhodamine B is calculated to be 28.3%. Comparative Example 2

[0032] Weigh 1 g of 3-amino-1,2,4-triazole into a crucible with a lid and calcine it at 500°C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times and then vacuum dried to obtain g-C3N5 monomer material.

[0033] Take 0.1 g of the prepared g-C3N5 monomer material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and illuminate for 30 minutes at a distance of 20 cm from the liquid surface. After centrifugation, the solution after degradation is measured by a UV-visible spectrophotometer at 554 nm. The degradation rate of rhodamine B is calculated to be 42.5%. Comparative Example 3

[0034] Weigh 5 g of nano-hydroxyapatite and 1 g of melamine, grind them in a mortar, transfer them into a crucible with a lid, and calcine them at 500 °C in a muffle furnace for 3 hours. The product is washed with deionized water 3 times and anhydrous ethanol 3 times, and then vacuum dried to obtain g-C3N4-modified nano-hydroxyapatite material.

[0035] Take 0.1 g of the prepared g-C3N4-modified nano-hydroxyapatite material and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. Directly turn on a 300-W xenon lamp light source (equipped with a λ≧420 nm filter) and irradiate the solution at a distance of 20 cm from the liquid surface for 30 minutes. After centrifugation, the solution after degradation has an absorbance of 554 nm determined by a UV-visible spectrophotometer. The degradation rate of rhodamine B is calculated to be 79.6%.

[0036] It can be seen from Comparative Examples 1 and 2 that the degradation rate of Rhodamine B by using single nanohydroxyapatite or g-C3N5 as a photocatalyst for visible light degradation is much lower than that of nanohydroxyapatite material modified by g-C3N5. This is because single nanohydroxyapatite can only absorb ultraviolet light, and visible light cannot excite it to produce photogenerated electrons and hole pairs. Although single g-C3N5 can excite photogenerated electrons and hole pairs under visible light, it is very easy to recombine and the photocatalytic reaction efficiency is not high. It can be seen from Comparative Example 3 that the photocatalytic activity can be greatly improved by modifying nanohydroxyapatite with g-C3N4, but there is still a large gap compared with the modification of g-C3N5. Characterization of g-C3N5 modified nano-hydroxyapatite materials

[0037] The present invention uses a D8 Advance X-ray diffractometer from Bruker Spectroscopy Instruments of Germany to characterize the g-C3N5 modified nanohydroxyapatite material prepared in Example 1 of the present invention and the g-C3N5 monomer material prepared in Comparative Example 2. The results are as follows: Figure 1 As shown, the test conditions are: Cu target Kα line, λ = 0.15406nm, 2θ is 10°~70°, and the scanning speed is 5(°) / min. Figure 1 It can be seen that the product of Comparative Example 2 is a g-C3N5 monomer, and the diffraction peaks at 12.8° and 27.5° at 2θ correspond to the (100) and (002) crystal planes, respectively. The characteristic peak at 27.5° is prominently reflected in the XRD spectrum of Example 1, and the characteristic peaks at other positions in the spectrum of Example 1 are all attributed to the (002), (211), (300), (301), (212), (302) and (202) crystal planes of nanohydroxyapatite, which is consistent with PDF card 09-0423. This result shows that the crystal structures of g-C3N5 and nanohydroxyapatite do not change after compounding, and the purity of the prepared material is high.

[0038] Figure 2 This is the energy band structure diagram of nano-hydroxyapatite material modified with g-C3N5. From the positions of the conduction band and valence band of each material in the figure, it can be seen that g-C3N5 and nano-hydroxyapatite materials form a dislocated energy band structure, which is beneficial to the further transfer of photogenerated electrons and holes from nano-hydroxyapatite to g-C3N5, thereby prolonging the carrier lifetime.

[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A g-C3N5 modified nano-hydroxyapatite material, characterized in that: include: The material consists of nano-hydroxyapatite and g-C3N5, wherein the nano-hydroxyapatite is a photocatalytic material matrix and the g-C3N5 is a modifier.

2. A method for preparing the g-C3N5 modified nano-hydroxyapatite material according to claim 1, characterized in that: The steps include: Nano-hydroxyapatite and 3-amino-1,2,4-triazole were weighed, ground in a mortar, and then transferred into a crucible with a lid. The mixture was calcined at 500° C. in a muffle furnace for 3 hours. The product was washed and vacuum dried to obtain g-C3N5-modified nano-hydroxyapatite material.

3. The preparation method according to claim 2, characterized in that: Nano-hydroxyapatite is commercially available or synthesized in the laboratory.

4. The preparation method according to claim 2, characterized in that: The mass ratio of nano-hydroxyapatite and 3-amino-1,2,4-triazole is (50~1):

1.

5. Use of a g-C3N5-modified nano-hydroxyapatite material obtained by the preparation method described in any one of claims 2 to 4 in removing environmental pollutants.

6. The use according to claim 5, characterized in that: The environmental pollutants include at least one of dyes such as rhodamine B and methylene blue.